1990
DOI: 10.1128/jvi.64.12.5738-5749.1990
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the herpes simplex virus type 1 65-kilodalton DNA-binding protein and DNA polymerase in the presence and absence of viral DNA synthesis

Abstract: Using indirect immunofluorescence, well-characterized monoclonal and polyclonal antibodies, and temperature-sensitive (ts) mutants of herpes simplex virus type 1, we demonstrated that the 65-kilodalton DNAbinding protein (65KDBP), the major DNA-binding protein (infected cel polypeptide 8 [ICP8]), and the viral DNA polymerase (Pol) colocalize to replication compartments in the nuclei of infected cells under conditions which permit viral DNA synthesis. When viral DNA synthesis was blocked by incubation of the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
2
35
1
Order By: Relevance
“…Localization of epitope-tagged UL5, UL8, and UL52 in infected cell nuclei. UL29, UL30, UL42, and UL9 all localize to replication compartments (14,30,31). Olivo et al were unable to detect a subnuclear localization of UL5, UL8, and UL52 with polyclonal antisera in an indirect immunofluorescence assay, perhaps because of the low sensitivity of the antisera they used (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Localization of epitope-tagged UL5, UL8, and UL52 in infected cell nuclei. UL29, UL30, UL42, and UL9 all localize to replication compartments (14,30,31). Olivo et al were unable to detect a subnuclear localization of UL5, UL8, and UL52 with polyclonal antisera in an indirect immunofluorescence assay, perhaps because of the low sensitivity of the antisera they used (30).…”
Section: Resultsmentioning
confidence: 99%
“…A polymerase null mutant virus forms prereplicative sites in the absence of PAA. Prereplicative sites can be found in the nuclei of cells infected with temperature-sensitive UL30 or temperature-sensitive UL42 mutants at the nonpermissive temperature or with a null mutant in UL30 (2,14,31). Thus, inactivation of the polymerase complex with drugs or by means of mutation leads to prereplicative site formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICP8 has also been reported to stimulate pol activity twofold (36,45), and one group has reported that it is required for UL42 to increase processivity of pol (26). Moreover, all three proteins colocalize to the same replication compartments in productively infected cells (2,11,22,23,43). It has been shown previously that the carboxy-terminal (C-terminal) 227 amino acids of pol are involved in and sufficient for complex formation with UL42 on the basis of coimmunoprecipitation of in vitro transcription-translation products with pol-specific antibody (13).…”
mentioning
confidence: 88%
“…Surrounded by vimentin, rough ER, mitochondria and polysomes. Chinchar et al, 1984;Darlington et al, 1966;Huang et al, 2006;Goorha, 1983, 1989;Zhao et al, 2007 Herpesviridae Barnard et al ., 1997;de Bruyn Kops et al ., 1998;Everett and Maul, 1994;Goodrich et al ., 1990;Jahedi et al ., 1999;Knipe et al, 1987;Lamberti and Weller, 1998;Leopardi et al ., 1997;Liptak et al, 1996;Markovitz and Roizman, 2000;Olivo et al ., 1989;Randall and Dinwoodie, 1986;Reynolds et al ., 2000;Taus et al ., 1998;Ward et al ., 1996 Contents of cellular origin RNA polymerase II, EAP ribosome component, proliferating cell antigen, retinoblastoma protein, p53, DNA ligase 1, DNA polymerase a, promyelocytic leukemia (PML), DNA-PKcs, Ku86 nonhomologous end joining, Bloom syndrome gene product, breast cancer-associated gene 1 protein, MSH2, Rad50, WRN RecQ helicase family member, BRG1 or BRM-associated factor 155, brahma-related gene-1 protein, brahma protein, histone deacetylase 2, hSNF2H, mSin3a, TATA binding protein (TBP), TBP-associated factors. Leopardi et al, 1997;Quadt et al, 2006;Taylor and Knipe, 2004;Wilcock and Lane, 1991 Nuclear sites of capsid assembly or assemblons…”
Section: Cytoplasmic Virus Factoriesmentioning
confidence: 99%